The role of upper body power in classical cross-country skiing performance - Alsobrook, N. G. (2005)
The purpose of this study was to evaluate the relationship between upper body power (UBP) and classical cross-country ski race performance. A group of experienced skiers (7 men, 3 women) completed 3 laboratory tests of UBP on a custom-built double poling ergometer: a 10-second test, a 60-second test, and an incremental test to exhaustion lasting 240-630 seconds. All subjects also competed in the West Yellowstone NorAm race on November 26, 2004. Unfortunately, the small subject number precluded any significant analysis of these data. A second group of skiers (10 men, 5 women) completed the same laboratory testing procedure and competed in the West Yellowstone Spam Cup race on December 11, 2004. Pearson`s product-moment correlation coefficients were calculated between average race speed (RS) and average 10-second power output (W10), average 60-second power output (W60), peak power output achieved during the incremental test (Wpeak), and peak oxygen uptake during the incremental test (VO2peak). After removal of 2 male subjects from the analysis, all 4 measures were found to correlate significantly with RS (r = .73-.95). Wpeak relative to bodyweight showed the highest correlation with RS (r = .95). When data was analyzed separately by gender, relative W10 was the best predictor of RS for women (r = .96) and absolute W10 was the best predictor of RS for men (r = .90). W10 and W60 were highly correlated with Wpeak for all subjects in both groups (r = .96 and .97, respectively). Regression analysis also indicated that a 5% improvement in relative Wpeak could decrease race time by as much as 39 seconds in a 10-km classical race. These findings suggest that both long and short term UBP are important for classical race performance, and that the factors determining short term UBP may be identical to those determining long term UBP.